Analysis of the Performance of Village Office Employees in Utilization Technology for Improving Administrative Services in Namohalu Esiwa, North Nias - Harefa, Feberni; Telaumbanua, Eliagus; Harefa, Idarni; Lase, Heseziduhu (Journal of International Multidisciplinary Research, 2024)
In this study, the main problem is how is the level of performance of Sisobahili Village office employees in the use of technology to improve administrative services in Sisobahili Village, Namohalu Esiwa District, North Nias Regency. This study aims to determine the level of performance of Sisobahili Village office employees in the use of technology to improve administrative services. This research uses a qualitative approach with a type of descriptive research, and the object of this study is carried out on natural objects. The data collection techniques used in this study are Observation, Documentation, and Interview. The researcher made observations by directly going into the field to see the object being studied. Then the researcher conducted interviews to explore information to data sources, namely the main informant, key informant, and supporting informant, then collected documents about the use of technology techniques in analyzing the data carried out in this study after data collection, then data reduction, data presentation, and conclusion or verification. Based on the results of the research, it was concluded that the Sisobahili Village Office still does not have adequate facilities to support administrative service activities to the community such as computers that are still not owned by the Sisobahili Village office, the facilities in the Sisobahili Village office, only in the form of laptops and printers . The limitations of these facilities are an obstacle for the Village apparatus in carrying out administrative activities related to the use of technology, so in this case information technology has not been used optimally. Human Resources in the use of information technology by the Sisobahili Village apparatus is still low, due to the low level of education of village apparatus in terms of technology utilization, so that some forms of services carried out still have obstacles, all forms of services related to technology are always charged to operators and other devices that are able to use technology, so it can be concluded based on the results of interviews at the level of human resources of the Village apparatus The use of technology is still minimal. The technology application system in Sisobahili Village has been running since 2018, but in 2022-2023, the Village information system, based semi-online, due to a lack of support, and for 2024 the plan will be carried out online through the website.